2020
DOI: 10.17306/j.jard.2020.01286
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the determinants, constraints and opportunities of smallholder farmers’ access to input markets: evidence from northern Ghana

Abstract: Smallholder farmers face multiple constraints in accessing input markets. This study seeks to understand the dynamics that influence input markets in northern Ghana and the opportunities that exist for smallholder farmers to increase their productivity and welfare. Using a random sample of 448 households, the study applied the probit and non-parametric methods in identifying the factors that influence farmers’ access to input markets and the key constraints faced by them. The results show that access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Additionally, though not significant, gender dynamics and farmers' group membership show noteworthy trends, suggesting the need for further investigation. Studies have shown that access to input markets (e.g., certified seeds) is likely influenced by various factors, including household wealth (livestock and land), access to finance and extension services (knowledge), distance to the nearest input market, and input source [5,9,10]. Efforts such as Cowpea Innovation Platforms (CIPs) that include financial institutions have helped smallholder farmers access loans and expand their crop production [8,20,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, though not significant, gender dynamics and farmers' group membership show noteworthy trends, suggesting the need for further investigation. Studies have shown that access to input markets (e.g., certified seeds) is likely influenced by various factors, including household wealth (livestock and land), access to finance and extension services (knowledge), distance to the nearest input market, and input source [5,9,10]. Efforts such as Cowpea Innovation Platforms (CIPs) that include financial institutions have helped smallholder farmers access loans and expand their crop production [8,20,35].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the national average cowpea yield is about 459.8 kg ha −1 , and 471 and 415 kg ha −1 in the Maradi and Zinder regions, respectively, but can be as low as 253.4 kg ha −1 in both regions [3,4]. These cowpea yields are extremely low due to poor soil fertility and, limited access to and use of inputs, including quality seeds, pest control methods, and fertilizers [5][6][7]. The use of quality seeds, particularly certified ones, can significantly increase cowpea yields, nearly doubling the overall crop productivity [8,9].…”
Section: Introductionmentioning
confidence: 99%